The role of natural gas in a low carbon Asia Pacific - Aguilera, Roberto F. (Elsevier, 2014)
As the Asia Pacific region continues to experience rapid economic growth, natural gas may have an important role in satisfying regional demand and transitioning to a low carbon economy. In this study, a Global Energy Market Model (GEM) is used to analyze the market shares of gases, liquids and solids in the Asia Pacific. The model matches the historical energy mix from 1850 to 2010 as well as the historical hydrogen to carbon (H/C) ratio. The GEM is then used to present scenarios of the Asia Pacific energy mix and H/C ratio to the year 2030. The scenarios vary according to policies and technologies that either encourage or discourage gas use. Estimates of conventional and unconventional gas quantities and costs are also presented, partly with a Variable Shape Distribution Model (VSD) and supply curves. The Asia Pacific is found to have vast natural gas resources, though suitable policies are needed to develop the potential. For instance, incentives will be necessary for investment in gas and LNG technology, as increased market share will not occur if investment does not take place in a timely fashion. In addition, it is important that government intervention not create disincentives for development of the regional gas and LNG industries.